Characterisation of a novel hybrid CFH/CFHR3 protein with impaired cell surface complement regulation in atypical haemolytic uraemic syndrome. (25th February 2016) - Wong, Edwin; Challis, Rachel; Harris, Claire; Goodship, Tim; Kavanagh, David
Abstract: Background: 60% of patients with atypical haemolytic uraemic syndrome have a rare genetic variant in C3, complement factor B ( CFB ), complement factor H ( CFH ), complement factor I ( CFI ), or CD46 . Many of these variants are in the 3' cell recognition domain of CFH . The genes encoding CFH and five CFH-related proteins are found adjacently in the regulators of complement activation (RCA) cluster on chromosome 1q32. This cluster is a region of genomic instability that can lead to genomic disorders causing atypical haemolytic uraemic syndrome. Methods: Using multiplex-ligation dependent probe amplification, we screened patients with atypical haemolytic uraemic syndrome who did not have a disease-causing genetic variant in C3, CFB, CFH, CFI, or CD46 for a genomic disorder. We used Sanger sequencing to define the breakpoint and identify a transcript for a hybrid CFH / CFHR3 gene. We purified the hybrid CFH / CFHR3 protein using allele specific monoclonal antibodies to the Y402H polymorphism of CFH . We tested its regulatory function using cell surface sheep erythrocyte lytic assays. Findings: We found one patient who had evidence of a de-novo deletion in CFH . We identified a 6·3 kb deletion extending from exon 20 of CFH to the CFH 3' intergenetic region incorporating exons 21, 22, and 23. Directly flanking the breakpoint was a 7 base-pair region of microhomology. A putative hybrid gene was predicted to include exons 1 to 20 of CFH and exons 2 to 6 of CFHR3 . We confirmed mRNA for a CFH / CFHR3 hybrid gene. Western blot analysis showed a hybrid CFH / CFHR3 protein at ∼160 kDa that lacked the cell recognition domain of CFH compared with 150 kDa for CFH. Peptide fragments from the larger band confirmed the CFH/CFHR3 hybrid protein. The purified CFH/CFHR3 hybrid protein showed less cell surface decay acceleration and cofactor activity compared with control. Interpretation: Screening for genomic disorders in this patient identified a hybrid CFH/CFHR3 protein that lacked cell surface regulation of complement. This valuable method has led to insight into the disease mechanism of atypical haemolytic uraemic syndrome, thus aiding in patient stratification for future management and prognosis. That the deletion was a de-novo event suggests that it is a dynamic region of the genome and that we can expect to discover further genomic disorders in atypical haemolytic uraemic syndrome. Funding: Medical Research Council, Wellcome Trust, EURenOmics.